PENGARUH DISIPLIN, MOTIVASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT EXPRAVET NASUBA DI KOTA BATAM - Fadhli Miftahussalam, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
The object of the study was conducted at the nose of PT Expravet Batam, which is engaged in animal husbandry. The purpose of this study was to determine how much influence the discipline, motivation and work stress provided by the company. What is provided by the company is good, which will lead to employee performance. The research method uses ordinary research in the form of cause and effect relationships of the variables studied, while the sampling technique used in this study is random sampling, which is sampling from members of the population that is carried out randomly without regard to strata in that regard. population. Consisting of 110 respondents, namely all employees working at PT Expravet Nasuba, the data source used to obtain data was a questionnaire because primary data was obtained directly from all employees. With SPSS (Statistical Package for the Social Sciences) version 25. Based on the results of the study, it shows that the coefficient of determination (R²) shows that discipline, motivation and Job Stress simultaneously affect employee performance by 92.5%, then the remaining 7.5% value explained by other factors not included in the research model.